Timepiece component made of polished titanium alloy

Through thermodynamic treatment and cold deformation steps, the problem of poor polishing effect of titanium alloy in watches or jewelry parts is solved, high-quality polishing surface and hardness improvement is achieved, and the application of titanium alloy in these fields is expanded.

CN119156462APending Publication Date: 2024-12-17ROLEX SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038762.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2023-05-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing titanium alloys have poor polishing effects in clocks or jewelry parts, resulting in defects and irregularities in the surface, limiting their application in these fields.

Method used

Thermodynamic treatment steps are adopted, including heat treatment at a temperature higher than the alpha phase transition temperature to obtain a structure that basically contains only the beta phase, followed by cold deformation and recrystallization heat treatment to reduce the beta phase grain size and at low temperatures The metastable ω phase is nucleated to promote the precipitation and uniform distribution of the α phase, thereby obtaining the optimal mechanical properties of the alloy and polished surface.

Benefits of technology

It achieves high-quality polishing effect on the surface of titanium alloy, reduces the surface roughness and hardness improvement, meets the high requirements of watches or jewelry, and expands the application potential of titanium alloy in these fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156462A_ABST
    Figure CN119156462A_ABST
Patent Text Reader

Abstract

The invention discloses a timepiece or jewelry part, characterized in that the timepiece or jewelry part comprises at least one part made of a titanium alloy, one surface of which is polished.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a timepiece or jewelry component comprising at least one part based on a titanium alloy. The invention also relates to a timepiece, for example, comprising such a timepiece component. Finally, the invention also relates to a method for manufacturing such a timepiece or jewelry component. Background Art

[0002] The choice of materials, in particular metals or metal alloys, is of great importance in the design of watch components. In fact, the metal or metal alloy must achieve the best possible compromise among numerous constraints, such as:

[0003] - Attractive appearance, without visible defects. For this purpose, precious metals are usually selected, which undergo very careful surface polishing to make them attractive.

[0004] - Exceptional mechanical properties, in particular high specific resistances, for example good fatigue resistance and excellent corrosion resistance; and good formability. In addition, it is also desirable to obtain sufficient hardness to minimize the risk of degradation of the surface state over time.

[0005] - Low density contributes to minimizing the overall weight of the timepiece.

[0006] Among the alloys that meet these constraints, titanium alloys are of interest, as they have a much lower density than other alloys (especially steel) while having globally impressive mechanical properties. However, the disadvantage of the titanium alloys used is that they have an inherently poor polishability, resulting in surface irregularities and defects. In order to avoid polishing defects on the surfaces of existing titanium alloys, satin or sandblasting treatments are usually chosen, thus limiting the possible surface appearance of such parts.

[0007] One of the objectives of the present invention is to define a technical solution that enables a wider application of titanium alloys in watch or jewellery parts, without being limited to the possibilities defined by the prior art. Summary of the invention

[0008] To this end, the invention is based on a timepiece or jewelry component, characterized in that it comprises at least one part made of a titanium alloy whose surface is polished.

[0009] The present invention is precisely defined by the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] These objects, features and advantages of the present invention will be described in detail in the following non-limiting description of a specific embodiment with reference to the accompanying drawings, in which:

[0011] Figure 1A first view of the surface of a titanium alloy part obtained by polishing a prior art titanium alloy is depicted.

[0012] Figure 2 A second view of the surface of a titanium alloy part obtained by polishing another prior art titanium alloy is described.

[0013] Figure 3 The steps of a method of manufacturing a titanium alloy component according to one embodiment of the present invention are schematically described.

[0014] Figure 4 The first two steps of a preferred embodiment of a method for manufacturing a titanium alloy component according to the present invention are schematically described.

[0015] Figure 5 The last two steps of the method of a preferred embodiment of manufacturing a titanium alloy component according to the present invention are schematically described.

[0016] Figure 6 An example of a mechanical spectroscopy measurement used by embodiments of the present invention is described.

[0017] Figure 7 depicts a surface view of a titanium alloy component obtained by polishing a titanium alloy according to the present invention;

[0018] Figure 8 Described are the measured values ​​of HV0.2 hardness as a function of annealing time obtained on Ti-5553 titanium alloy samples obtained using a method according to an embodiment of the present invention (steps 1-4) and according to an optional method (steps 1-2+4, excluding step 3), respectively.

[0019] Fig. 9 The measurement of roughness Rx using standardized parameters Rt, Rz and Ra obtained on Ti-5553 titanium alloy samples obtained using a method according to an embodiment of the present invention (steps 1-4) and two optional methods (having steps 1-2+4, excluding step 3; and having steps 1-2, without steps 3-4, respectively) is described.

[0020] Fig.10 The results of observation of the Ti-4733 titanium alloy obtained by the method according to one embodiment of the present invention (steps 1-4) using a transmission electron microscope (TEM).

[0021] Fig.11 The Ti-4733 titanium alloy obtained according to another method (steps 1-2+4) was observed using a transmission electron microscope (TEM).

[0022] Fig.12The results of observing the Ti-4733 titanium alloy obtained by the method according to one embodiment of the present invention (steps 1-4) using a scanning electron microscope (SEM).

[0023] Fig.13 The Ti-4733 titanium alloy obtained according to another method (steps 1-2+4) was observed using a scanning electron microscope (SEM). DETAILED DESCRIPTION

[0024] In this document, the expression "based on an alloy" will be used for any part consisting of at least 50% by weight of the alloy concerned.

[0025] The present invention relates to a timepiece or jewelry component comprising at least one component made of or based on a titanium alloy, wherein the titanium alloy extends over at least a portion of the visible surface of said component. The invention will define a method making it possible to obtain titanium alloys having new properties and to obtain surface states having an attractive aesthetic appearance, in particular making it possible to obtain, in a convenient and desirable manner, a polished surface of similar quality to that obtained using another alloy, in particular steel.

[0026] According to the present invention, it was found that the titanium alloys of the prior art used for watch applications have two phase forms: α phase and β phase. The α phase corresponds to a hexagonal crystal structure, and the β phase corresponds to a central cubic crystal structure. The difference in the mechanical properties of these two phases creates problems when finishing the surface of the titanium alloy, such as Figure 1 As shown in , after attempted polishing, the titanium alloy surface still has a visible β phase grain microstructure, which results in an "orange peel" appearance; and / or abrasive embedded in the ductile β phase, resulting in Figure 2 Scratches and imperfections shown. Figure 1 , 2 and Figure 7 It is obtained by reflection imaging of the dark and bright surface patterns of titanium alloy samples, which can observe polishing defects.

[0027] Because of this, it is not currently possible to obtain a satisfactory polishing finish on titanium alloy surfaces for the high demands of watches and jewelry. This difficulty is particularly evident on extended surfaces (e.g., dials, bracelet links, buckles, etc.). This limits the use of titanium alloys on satin-finished or sandblasted surfaces. Therefore, there is currently no method for polishing the surface of a watch or jewelry component made of titanium alloy, nor is there an effective manufacturing method using a watch or jewelry component finish that includes a polishing step. Therefore, there is no watch that has such a polished titanium alloy surface on most or even the entire visible surface, which seriously limits the use of titanium alloys in watches and jewelry.

[0028] The invention is therefore based on a method for the total or partial manufacture of a component made of or based on a titanium alloy, which method in particular makes possible a step of polishing the surface made of or based on the titanium alloy of said component in a manner compatible with the high requirements of timepieces or jewellery.

[0029] In one embodiment of the present invention, the manufacturing method is based on a thermodynamic processing step comprising the following steps: Figure 3 As shown in the figure:

[0030] - heat treatment of the titanium alloy at a temperature higher than the transformation temperature Tβ from the α phase to the β phase, followed by cooling to obtain a structure comprising essentially only β phase grains (step 1, homogenization);

[0031] - a continuous deformation treatment cycle or at least one deformation treatment cycle, in particular cold deformation, and a recrystallization heat treatment at a temperature slightly above the transformation temperature from the α phase to the β phase, in order to maintain a structure consisting essentially only of β phase grains while reducing the size of the β phase grains (step 2);

[0032] - Through low temperature heat treatment, the metastable ω phase is nucleated or precipitated (step 3);

[0033] - Heat treatment at an intermediate temperature higher than the low temperature of nucleation of the ω phase and lower than the transformation temperature from the α phase to the β phase, so as to obtain the growth (or precipitation) of the α phase that will harden the titanium alloy (step 4). In other words, the nucleation of the ω phase acts on the precipitation of the seeds of the α phase.

[0034] Figure 4 The execution of the first two steps of the method according to a particularly advantageous embodiment is schematically described.

[0035] First, the heat treatment step is advantageously carried out at a temperature between 0°C and 100°C, preferably between 10°C and 50°C, above the transformation temperature Tβ from the α phase to the β phase, and preferably under a protective atmosphere. This first step makes it possible to obtain a microstructure of the titanium alloy consisting entirely of the β phase. Cooling by quenching TR makes it possible to fix the β phase at room temperature. The processing time t is relatively short, ideally 30 minutes or less, to limit the growth of the β phase grains and to obtain the smallest possible grain size. This step also enables the titanium alloy to be homogenized.

[0036] In other words, this first homogenization step can dissolve the alpha phase present in the material. Rapid cooling from the complete beta phase structure can fix the structure in the alloy without forming a martensite phase at room temperature. The complete beta phase structure has sufficient ductility to carry out the subsequent deformation step, which will enable recrystallization.

[0037] In this embodiment, the second step in the continuous deformation cycle includes a continuous cold deformation cycle (D) and a recrystallization heat treatment (RX). The purpose of this step is to obtain a microstructure that still contains the maximum amount (ideally 100%) of β phase and the minimum amount (ideally no) of α phase and the smallest possible grain size. In fact, it is difficult to deform the material in the presence of α phase, which is the hardest and will produce cracks during the deformation process. Therefore, it is difficult to reduce the size of the β phase grains in the presence of α phase. The method selected by the present invention overcomes this difficulty by acting on an alloy composed entirely of β phase. Of course, the method can be carried out in the presence of a small amount of α phase, preferably less than 10% by volume. The heat treatment advantageously causes the titanium alloy to be exposed to a temperature slightly higher than Tβ for a short time, followed by immediate TR quenching. The temperature can be between Tβ and Tβ+20°C and includes the end value. For the typical size of the external parts of the watch, the duration is preferably between 3 minutes and 10 minutes and includes the end value, but must be suitable for the size of the treated parts. Multiple cycles can be performed in succession to refine the grains. Alternatively, a single cycle may be sufficient. Advantageously, 2 to 10 cycles, or even 2 to 5 cycles, are performed.

[0038] In the second step, the deformation treatment of the titanium alloy part introduces dislocations in the alloy, which induce recrystallization in the form of finer grains during the heat treatment. Cold deformation treatment (e.g., room temperature rolling or cold forging) is advantageous for this deformation. These cold deformation methods are advantageous because they are easy to control. Nevertheless, it is also feasible to use hot deformation methods (e.g., forging or uniaxial deformation at high temperatures). In summary, the effect of this second step is therefore to reduce the size of the microstructure as much as possible, more precisely the size of the microstructure of the β-phase grains.

[0039] Figure 5 The last two steps of the method according to a particularly advantageous embodiment are schematically described.

[0040] The third step of ω phase nucleation advantageously comprises a heat treatment Tω of less than 4 hours at a temperature between 150° C. and 350° C., inclusive, in particular a heat treatment Tω of between 250° C. and 330° C., inclusive, for between 2 and 4 hours, inclusive. The heat treatment step at low temperature nucleates the metastable ω phase, which will appear uniformly in the titanium alloy. This is conducive to the use of the ω phase grains as nucleation points for future growth of the α phase.

[0041] In fact, step 4 (precipitation of α phase) comprises a heat treatment Tα between 1 hour and 3 hours and including the end value at a temperature between 350°C and 650°C, including the end value; or even a heat treatment Tα between 1 hour and 3 hours and including the end value at a temperature between 500°C and 600°C, including the end value. This step allows the α phase to finally appear in the titanium alloy. The advantage of growing (precipitating) the α phase by making the ω phase form a seed crystal is that the α phase is obtained to be uniformly and finely distributed (ideally on a submicron scale, even with a maximum size between 1 and 10 μm) in the alloy. The structure obtained in this way is advantageously a non-laminar structure. Moreover, precipitation at the grain boundaries, even if it may occur, does not constitute the main part of the α phase.

[0042] It should be noted that the third step is described as a single, independent step. Alternatively, it can also be included in the temperature increase process of the fourth step, that is, it corresponds to a sub-step of the fourth step.

[0043] The above method can obtain an alloy that optimally combines the two phases, α and β, each phase contributing advantages to the alloy without the disadvantages of the prior art.

[0044] In fact, the alpha phase allows alloys to achieve satisfactory hardness, while alloys with only the beta phase would be too soft. The good distribution of the alpha phase and its nanometer size therefore contribute to obtaining the best hardness for this alloy. Low hardness is important to be able to apply polishing steps, which would damage the surface if the material was too soft. The hardness itself also contributes to maintaining the quality of the surface state over time. To illustrate these characteristics, Figure 8 An example of HV0.2 hardness measurement data obtained on a Ti-5553 titanium alloy sample obtained using a method according to an embodiment of the present invention (steps 1-4) and an optional method (steps 1-2+4, without step 3) as a function of annealing time t at a temperature of 550°C in step 4 is described.

[0045] There is a large and significant difference of more than 50 HV between the sample according to an embodiment of the present invention and the sample without step 3 of the method according to an embodiment of the present invention for the same annealing time. In general, the precipitation of a very fine α phase induced by the method according to the present invention makes it possible to increase the typical hardness by 50 HV compared to the alternative method. Therefore, the precipitation of a very fine α phase induced by the method according to the present invention makes it possible to increase the hardness by more than 450 HV, or even more than 500 HV, depending on the titanium alloy considered and the hardness obtained by the alternative method. For comparison, the hardness of titanium alloys without α phase is lower than 300 HV: for example, the hardness of a sample obtained using the alternative method (only steps 1-2, corresponding to a sample obtained by quenching from the β phase and without the generation of α phase) was measured and showed a hardness of 291 HV0.2. The hardness of titanium alloys containing both α and β phases under the prior art is lower than 400 HV. The uniform distribution of α phase grains can also prevent carbide particles used for polishing from being embedded in the alloy and damaging the surface (such as Figure 2 The proportion of the α phase is advantageously between 35% and 55% by volume, inclusive, or even between 35% and 65% by volume, inclusive.

[0046] The β phase plays a decisive role in the reflectivity of the surface. Large-sized β phase grains may, for example, have a different reflectivity, which can impair the visual appearance of the surface obtained. In fact, if these β phase grains are too large, they form irregularities on the surface that are visible to the naked eye during polishing of the surface. The method can minimize the size of the β phase grains. Moreover, the method makes it possible to homogenize the distribution of the α phase in the β phase grains.

[0047] Finally, if Figure 7 As described in , the titanium alloy structure obtained makes it possible to form a high-quality polished surface using conventional polishing techniques.

[0048] As explained above, the various steps of the method are carried out under specific temperature conditions selected to control the structure of the titanium alloy. It should be noted that these temperature values ​​depend on the composition of the titanium alloy used. Therefore, pre-defining fixed temperature values ​​is not the best solution, but it is advantageous to select the appropriate temperature for each alloy to implement the method according to this embodiment in the best way.

[0049] The method according to this embodiment of the invention therefore comprises one or more sub-steps of determining the optimum temperatures to be considered, in particular transformation temperatures, such as the temperatures of seeding and recrystallization of the ω and α phases.

[0050] To this end, an advantageous embodiment is based on the use of mechanical spectroscopy or internal friction. Measuring the internal friction allows observing the energy dissipation associated with the movement of defects (e.g. dislocations, grain boundaries or local defects in the microstructure). If the mobility of these defects depends on temperature, it is possible to detect the temperature at which the defects start to move in the alloy. Considering that both nucleation and recrystallization phases require microstructural transformations, mechanical spectroscopy can be used to detect the temperature at which they occur. For example, Figure 6 The internal friction curve of the undeformed sample of Ti-4733 titanium alloy shown in FIG. 1 can identify the nucleation phenomenon of the phase and / or the recrystallization phenomenon of the alloy as a function of temperature. The various structural changes that are worth noting and using in the method according to the embodiment of the present invention correspond to different peaks and shoulders of the curve. For example, the curve can determine the temperature at which the ω phase and the α phase can be nucleated, which are Figure 6 In the graph, the positions of the peaks are obtained by deconvolution. More precisely, the deconvolution of the mechanical spectroscopy measurement can be performed with a constant baseline, a base that varies according to an exponential function of temperature, and an Arrhenius-type function applied to at least one peak, and finally the temperature is extracted. Therefore, by measuring the internal friction phenomena of the alloy by mechanical spectroscopy, the temperatures corresponding to the various phenomena used in the various steps of the present invention can be accurately defined.

[0051] In particular, the nucleation of the ω phase in titanium alloys can be detected by mechanical spectroscopy, which is very difficult to identify by other methods. Moreover, the advantage of mechanical spectroscopy is that it can be used in real time, enabling the alloy to be observed "in situ".

[0052] The work carried out by the inventors thus shows that mechanical spectroscopy is a suitable technique for determining transformation temperatures in titanium alloys, which, to their knowledge, has not been recognized so far. Surprisingly, it is possible to determine the formation seed peak in titanium alloys, which enables the practical use of the method according to the invention and the obtaining of a titanium alloy according to the invention. More generally, for any titanium alloy having an α+β phase microstructure at the temperature of use, it is advantageous to adopt a step of determining the transformation temperature and / or recrystallization temperature of said titanium alloy by mechanical spectroscopy, in particular determining the nucleation temperature of the ω phase, even the nucleation temperature of the α phase, even the recrystallization temperature. A first effect that can be obtained with an optimized embodiment of the method according to the invention consists in a maximum surface hardness, such as Figure 8 As shown in .

[0053] Alternatively, the nucleation of the ω phase can be shown by transmission electron microscopy, especially electron diffraction which shows the unique appearance of the crystal structure of the ω phase. Another technique that can be used is to measure the electrical resistance, which will change slightly when the ω phase precipitates. These other detection techniques are more complicated to implement and / or less accurate methods.

[0054] Finally, the mechanical spectroscopic measurements facilitate the optimization of the treatment duration and treatment temperature for each given alloy and for each step of the method according to an embodiment of the invention. It should be noted that for some steps of the method, the treatment time and temperature values ​​remain comparable from one alloy to another.

[0055] The following table illustrates some tests of the method, in whole or in part, using certain titanium alloys. The table first shows the important effect of the third step of the method. In fact, some tests carried out by removing the third step gave bad results, more precisely, the surface no longer responded satisfactorily to the polishing step. On the contrary, the use of the invention as described above enables very good results to be achieved, in particular very good polishing effects.

[0056]

[0057] Fig. 9 Represents the roughness measurements Rt, Rz and Ra (the values ​​of Ra on the bar graph are multiplied by 10) obtained on Ti-5553 alloy samples obtained using, respectively, a method according to an embodiment of the invention (steps 1-4) and two alternative methods (using, respectively, only steps 1-2+4 without step 3; and using only steps 1-2 without steps 3 and 4). The three roughness parameters considered are measured and calculated according to the ISO 21920 standard, where Rt, known as the total height: the distance between the deepest and highest points of all the profiles considered; Rz, known as the maximum height: the average of the maximum distances between the deepest and highest points on all the profiles; and Ra, known as the arithmetic mean height, the length of the profile concerned being 0.8 mm. The sample used in the alternative method ("steps 1-2") corresponds to a sample quenched from the β phase, in which no α phase is formed and has a low hardness of less than 300 HV 0.2. The sample used in the alternative method ("steps 1-2+4") corresponds to a quenched sample in the β phase, then annealed at a high temperature of 550°C, where the α phase precipitates in the β phase grains at the grain boundaries, and the hardness increases significantly. The sample according to the invention ("steps 1-4") corresponds to a sample quenched in the β phase, then annealed for the first time at a moderate temperature of 290°C to precipitate the ω phase, and annealed for the second time at a high temperature of 550°C to form the α phase in the β phase grains, and exhibits the highest hardness. For the three roughness parameters considered, the roughness of the samples according to the invention is much lower than that of the samples obtained using the alternative method. Therefore, the optimized implementation of the method according to the invention makes it possible to obtain a minimum surface roughness as a second effect.

[0058] More specifically, when the third step of the method is omitted, the maximum height difference between various β-phase grains measured on the polished surface (the measurement area is typically 1.5×1.5 mm 2 ) of about 100 nm, as shown by the measurement of the roughness parameter Rz; therefore, the expert judged that the polishability was very general, manifested as visible "orange peel"-like areas. When the third step was used, the α phase areas were of very small size, with a hardness of 472 HV. In addition, as shown by the measurement of the roughness parameter Rz, the maximum difference between the measured average heights of the various β phase grains on the polished surface was about 50 nm, which is the height difference obtained without the use of the third step divided by 2, so this can significantly improve the polishability of the surface, in particular to obtain a satisfactory polished appearance, in particular without the orange peel effect and without embedded abrasive particles.

[0059] Fig.10 Describes the observation results of a titanium alloy sample Ti-4733 obtained by the method according to the present invention using a dark field transmission electron microscope (TEM), wherein the sample is along <110> The zone axis is aligned and one of the beams diffracted by the α phase is selected.

[0060] Samples obtained by alternative methods (steps 1-2+4) (e.g. Fig.11 The results shown in Figure 4, where step 4 is carried out at a low temperature (390°C, 1 hour) in the recommended range, show very extensive α phase grain growth in a given preferred direction with a very inhomogeneous distribution. Therefore, if the seeding and growth heat treatment of the α phase is carried out in a single step, the α phase is very inhomogeneous with very elongated grains, with a length of more than 500nm in its largest dimension, as shown in Figure 4. Fig.11 The sample according to the present invention (steps 1-4) (a step of seeding the ω phase at 240°C before annealing at 390°C for 1 hour in step 4) shows uniformly dispersed very fine α phase grains. It should be noted that the results of transmission electron microscopy after step 3 and before step 4 show the presence of the ω phase but not the α phase.

[0061] Fig.12 The observation results of the Ti-4733 titanium alloy sample obtained by the method according to the present invention using a scanning electron microscope (SEM) are described. Fig.13 The sample obtained by the alternative method shown in (steps 1-2+4, where step 4 is performed again at a temperature of 600°C) shows very extensive α-phase grain growth with a very inhomogeneous distribution. This sample can be regarded as Fig.11The logical continuation of the sample in step 4, the higher the temperature in step 4, the more favorable the growth of the α phase. The sample according to the present invention (steps 1-4, ω phase seeding step at 240°C for 1 hour before annealing at 600°C in step 4) shows clear, finer and uniformly dispersed α phase grains. These TEM and SEM observations clearly show the importance of the α phase (and therefore step 3 according to the present invention) for obtaining an α phase with uniformly dispersed very fine grains.

[0062] The table above also shows that some alloys such as Ti-4733 and Ti-5553 are very suitable for obtaining a satisfactory polished appearance. Other alloys such as Ti-15-3, Ti-15.9V-3Cr-3.6Al-3Sn are not so suitable.

[0063] The above table also shows various conditions of certain steps that can produce equivalent results. It can be seen that for the third step of the present invention, conditions between (300°C, 1 hour) and (350°C, 3 hours) have been successfully tested.

[0064] In general, the time and temperature parameters of the method are interchangeable to some extent, for example, a higher temperature applied for a shorter time can obtain comparable results compared to a lower temperature applied for a longer time. Therefore, those skilled in the art will find favorable conditions in the selection of temperature / time groups from the following general range. In order to precipitate the ω phase (the third step of the method), it may be appropriate to carry out at a low temperature between 150°C and 350°C and include the end values ​​for up to 4 hours; it may even be appropriate to carry out at a low temperature between 250°C and 330°C and include the end values ​​for between 2 hours and 4 hours and include the end values. In order to obtain the precipitation of the α phase (the fourth step of the method), the temperature / time group can be fixed between (500°C, 1 hour) and (600°C, 3 hours). Therefore, the above-mentioned condition group can be adjusted and should not be regarded as a fixed and absolute limitation.

[0065] In addition to the above steps 1 and 2, there may be other options to obtain a microstructure formed by small-sized β-phase grains. In particular, forging and hot deformation can be performed at a temperature below Tβ or at a temperature above Tβ. In this deformation method, α-phase grains may already exist, and the purpose is to refine the β-phase grains as much as possible through deformation. Steps 3 and 4 (especially step 3 of ω-phase seed formation) remain unchanged. In another variation, step 3 of ω-phase seed formation can also include forging and deformation to combine mechanical grain refinement with the formation of uniformly dispersed very fine ω-phase grains.

[0066] Finally, the invention also comprises a method for manufacturing a timepiece or jewellery component, characterised in that it comprises a finishing step of polishing the titanium alloy surface of the component.

[0067] According to the embodiment of the manufacturing method described, it can be implemented with any titanium alloy. However, it should be noted that some titanium alloys have a more favorable structure than other titanium alloys, which makes it possible to obtain the best results, especially in terms of polishability. In order to be able to use the method according to the invention, these alloys contain alloying elements that stabilize the β phase at room temperature. For example, Ti-5553 or Ti-4733 alloys; even Ti-5553 or Ti-4733 or Ti-10-2-3 or Beta-C or VT22 or Ti-1-8-5 or Ti-8823 alloys; even Ti-5553 or Ti-4733 or Ti-10-2-3 or Beta-C or VT22 or Ti-1-8-5 or Ti-8823 or Beta21 S or Timetal21S or Betalll or TMA, produce very good results.

[0068] In general, it seems that titanium alloys that meet the following range 8≤MoE≤11, or even 8.3≤MoE≤10.0 (wherein MoE is molybdenum equivalent) react particularly well during implementation of the method according to an embodiment of the present invention. The molybdenum equivalent (MoE) takes into account the effects of various elements on stabilizing the β phase by using the following formula: MoE=1.0 (wt% Mo) + 0.67 (wt% V) + 0.44 (wt% W) + 0.28 (wt% Nb) + 0.22 (wt% Ta) + 2.86 (wt% Fe) + 1.67 (wt% Cr) + 1.25 (wt% Ni) + 1.70 (wt% Mn) + 1.70 (wt% Co) + 0.77 (wt% Cu) + 0.78 (wt% Sn) - 0.17 (wt% Zr) - 1.0 (wt% Al).

[0069] In addition or alternatively, titanium alloys can also be characterized using the Bo and Md parameters, where Bo and Md are the bond order and the average d-orbital energy level defined by Morinaga, respectively (see M. Morinaga, Molecular Orbital Theory and Its Application in the Design of Biomedical Titanium Alloys, Titanium in Medical and Dental Applications, edited by FH Froes and M. Qian, Woodhead Publishing, 2018), and are calculated using the following formulas: Md = 2.447(at% Ti) + 1.961(at% Mo) + 1.872(at% V) + 2.072(at% W) + 2.424(at% Nb) + 2.531(at% Ta) + 0.969(at% Fe) + 1.478(at% Cr) + 0.724(at% Ni) + 1.194(at% Mn) + 0.807(at% Co) + 0.567(at% Cu) + 2.100(at% Sn) + 2.934(at% Zr) + 2.200(at% Al); Bo = 2.79(at% Ti) + 3.063(at% Mo) + 2.805(at% V) + 3.125(at% W) + 3.099(at% Nb) + 3.144(at% Ta) + 2.651(at% Fe) + 2.779(at% Cr) + 2.412(at% Ni) + 2.723(at% Mn) + 2.529(at% Co) + 2.114(at% Cu) + 2.283(at% Sn) + 3.086(at% Zr) + 2.426(at% Al). Thus, it seems that titanium alloys within the following ranges 2.755 < Bo < 2.810 and 2.33 < Md < 2.44, or even 2.758 < Bo < 2.788 and 2.330 < Md < 2.385, or even 2.765 < Bo < 2.775 and 2.36 < Md < 2.38 perform particularly well during the implementation of the method according to an embodiment of the present invention.

[0070]

[0071] According to the method of the present invention, high hardness and fine microstructure can be obtained simultaneously, so good polishability and low roughness can be obtained after polishing. The seed formation and growth of the α phase are controlled by two annealing steps (steps 3 and 4), preferably based on a fine β phase grain microstructure. The size of the β phase grains is determined by the recrystallization and deformation steps, and the size of the α phase grains is determined by the formation of seeds from the ω phase at the beginning (annealing in step 3) and then by additional annealing at a second time (step 4). The temperature and duration of each annealing step can be determined by measuring the characteristics of the alloy using mechanical spectroscopy. The controlled growth of the ω phase induces the appearance of uniformly distributed and very small ω phase grains without the simultaneous generation of the α phase or the formation of α phase seeds. Therefore, the α phase that forms seeds and grows during the subsequent annealing is also very small and uniform, such as Fig.10 , 12 Observation results show.

[0072] The invention also relates to a timepiece or jewellery component, characterised in that it comprises at least one part made of or based on a titanium alloy, wherein the surface of the titanium alloy is polished. In fact, as discussed above, the invention makes it possible to produce a titanium alloy whose polishing is particularly compatible with the high requirements of the timepiece or jewellery sector.

[0073] This polishing property can be defined by the difference in the average height of the β-phase grains on the polished titanium alloy surface, which may be less than 150nm, even less than 120nm, or even less than 100nm. In addition or alternatively, this polishing property can also be defined by a roughness parameter Rz, which corresponds to the maximum distance between the highest point and the lowest point observed in all tested profiles, which may be less than 90nm, even less than 80nm, or even less than 60nm. In addition or alternatively, this polishing property can be defined by the roughness parameter Ra defined by the above standard, and its value is less than 15nm, even less than 12nm, or even less than 10nm. The present invention is not limited to the polishing property defined by the exact value of the roughness.

[0074] In other words, the watch or jewelry component according to the present invention may include at least one component made of a titanium alloy, the titanium alloy including grains, in particular β-phase grains, wherein the surface of the titanium alloy is polished, characterized in that the difference in average height of the grains, in particular β-phase grains, of the polished surface of the titanium alloy is less than 150nm and / or the average total roughness Rz of the polished surface is less than 90nm and / or the arithmetic mean roughness Ra of the polished surface is less than 15nm; or characterized in that the difference in average height of the grains, in particular β-phase grains, of the polished titanium alloy surface is less than 120nm and / or the average total roughness Rz of the polished surface is less than 80nm and / or the arithmetic mean roughness Ra of the polished surface is less than 12nm; or characterized in that the difference in average height of the grains, in particular β-phase grains, of the polished titanium alloy surface is less than 100nm and / or the average total roughness Rz of the polished surface is less than 60nm and / or the arithmetic mean roughness Ra of the polished surface is less than 10nm.

[0075] The titanium alloy of the component can be selected from the list given above. In general, the titanium alloy obtained achieves a good compromise between all the constraints mentioned at the beginning of this article. In addition to its polishability, it is hard, strong and light.

[0076] The titanium alloy of the present invention advantageously comprises β-phase grains having an average size of less than or equal to 50 μm, even less than or equal to 45 μm or 40 μm. This size can alternatively be less than or greater than or equal to 25 μm, even greater than or equal to 35 μm.

[0077] The titanium alloy advantageously comprises an α phase uniformly distributed in β phase grains.

[0078] The component also comprises a titanium alloy having advantageously a hardness greater than or equal to 400 HV, even greater than or equal to 450 HV, even greater than or equal to 470 HV. The hardness may be between 400 and 600 HV and inclusive, even between 450 and 550 HV and inclusive, even between 470 and 500 HV and inclusive.

[0079] The invention is applicable to a watch or jewelry component entirely composed of the above-mentioned titanium alloy. Alternatively, the component may only include parts made of the above-mentioned titanium alloy. Alternatively, it may be based entirely or partially on such a titanium alloy. For example, in one embodiment, the titanium alloy accounts for at least 75% of the volume of the component. In another embodiment, the component includes at least one part including the polished surface, the polished surface being entirely made of the titanium alloy; and / or having a thickness greater than or equal to 0.1 mm, that is, the part is not a simple thin surface coating, but forms a solid volume.

[0080] On the other hand, the watch component according to the present invention is advantageously an external part of a watch, in particular a watch case component, for example, a dial, a back, a bezel, a crown or a crown cover. It can also be a bracelet component or a clasp component such as a link, an edge link, a center link, a link, a clasp piece, a clasp cover or a clasp link, etc.

[0081] The present invention also relates to a timepiece, in particular a wristwatch, characterized in that it comprises at least one timepiece assembly as described above.

Claims

1. A watch or jewelry component, characterized in that: The clock or jewelry component includes at least one part made of a titanium alloy, and the surface of the titanium alloy is polished.

2. A timepiece or jewellery component according to the preceding claim, characterised in that The arithmetic mean roughness Ra of the polished surface is less than 15 nm, even less than 12 nm, and even less than 10 nm.

3. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The mean total roughness Rz of the polished surface is less than 90 nm, or even less than 80 nm, or even less than 60 nm.

4. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The titanium alloy contains grains, especially β-phase grains; and the difference in the average height of the grains, especially β-phase grains, on the polished titanium alloy surface is less than 150 nm, or even less than 120 nm, or even less than 100 nm.

5. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The titanium alloy conforms to the following ranges: 8 ≤ MoE ≤ 11, or even 8.3 ≤ MoE ≤ 10.0; and / or the following ranges: 2.755 < Bo < 2.810 and 2.33 < Md < 2.44, or even 2.758 < Bo < 2.778 and 2.330 < Md < 2.385, or even 2.765 < Bo < 2.775 and 2.36 < Md < 2.38, where MoE is the molybdenum equivalent, and Bo and Md represent the bond order and the average d-orbital energy level respectively.

6. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The titanium alloy contains β-phase grains with an average size less than or equal to 50 μm.

7. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The titanium alloy contains β-phase grains and α-phase grains, and the α-phase is uniformly distributed in the β-phase grains.

8. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The titanium alloy contains β-phase grains and α-phase grains, and the amount of the α-phase is between 35 vol% and 55 vol% including the end values, or even between 35 vol% and 65 vol%.

9. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The titanium alloy is a Ti-5553, Ti-4733, Ti-10-2-3, Beta-C, VT22, Ti-1-8-5, Ti-8823, Beta21S, Timetal21S, BetaIII or TMA alloy.

10. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The hardness of the titanium alloy is greater than or equal to 400 HV, or even greater than 450 HV, or even greater than or equal to 470 HV, or between 400 HV and 600 HV including the end values, or even between 450 HV and 550 HV including the end values, or even between 470 HV and 500 HV including the end values.

11. The clock or jewelry component according to any one of the preceding claims, characterized in that: - The titanium alloy accounts for at least 75% by volume of the component; and / or - The clock or jewelry component includes at least one part that includes the polished surface made entirely of the titanium alloy and having a thickness greater than or equal to 0.1 mm; or - The clock or jewelry component is made entirely of the titanium alloy.

12. A timepiece or jewellery component according to any one of the preceding claims, characterised in that The clock or jewelry component is a clock, especially an external part of a watch, especially a case component such as a dial, a back case, a bezel, a crown or a crown cover; or especially a bracelet component or a clasp component such as a link, an edge link, a center link, a link, a clasp piece, a clasp cover or a clasp link.

13. A timepiece, in particular a wristwatch, characterized in that: The clock includes the clock component according to any one of the preceding claims.

14. A method for manufacturing a watch or jewelry component, characterized in that The method includes a step of heat-treating at least one part made of a titanium alloy of the component, and the heat-treatment step includes a thermomechanical treatment of the titanium alloy, which includes a step of nucleating a metastable ω-phase serving as a seed crystal for precipitating the α-phase.

15. Method for manufacturing a timepiece or jewellery component according to the preceding claim, characterised in that The step of nucleating the metastable ω-phase includes: performing a heat treatment at a temperature between 150 °C and 350 °C and including the end values; and the method then includes a step of precipitating the α-phase by performing a heat treatment at a temperature higher than the nucleation temperature of the ω-phase and lower than the transformation temperature from the α-phase to the β-phase, at a temperature between 350 °C and 650 °C and including the end values, or even at a temperature between 500 °C and 600 °C and including the end values.

16. Method for manufacturing a timepiece or jewellery component according to claim 14 or 15, characterised in that The thermomechanical treatment includes a previous step of producing a microstructure of the titanium alloy containing β-phase grains with an average size less than or equal to 50 μm.

17. Method for manufacturing a timepiece or jewellery component according to the preceding claim, characterised in that The previous step includes the following steps: - Performing a heat treatment at a temperature higher than the transformation temperature from the α-phase to the β-phase of the titanium alloy; - A continuous cyclic deformation treatment or at least one cyclic deformation treatment, in particular a cold deformation treatment, and a recrystallization heat treatment at a temperature slightly higher than the transformation temperature from the α-phase to the β-phase of the titanium alloy.

18. Method for manufacturing a timepiece or jewellery component according to the preceding claim, characterised in that The steps before the thermomechanical treatment of the titanium alloy include the following steps: - Performing a heat treatment at a temperature between 10 °C and 100 °C, in particular between 10 °C and 50 °C, at a temperature slightly higher than the transformation temperature from the α-phase to the β-phase, and then cooling to obtain a structure containing substantially only β-phase grains; - The continuous deformation treatment cycle or at least one deformation treatment cycle includes performing a recrystallization heat treatment at a temperature at most 20 °C higher than the transformation temperature from the α-phase to the β-phase to maintain a structure containing substantially only β-phase grains while reducing the size of the β-phase grains; The step of nucleating the metastable ω-phase is carried out by performing a heat treatment at a low temperature between 150 °C and 350 °C and including the end values for 4 hours or less, in particular by performing a heat treatment at a low temperature between 250 °C and 330 °C for 2 to 4 hours; The method then includes a step of precipitating the α-phase, that is, by performing a heat treatment at an intermediate temperature higher than the nucleation temperature of the ω-phase and lower than the transformation temperature from the α-phase to the β-phase, by performing a heat treatment between 350 °C and 650 °C for between 1 hour and 3 hours and including the end values, or even by performing a heat treatment between 500 °C and 600 °C for between 1 hour and 3 hours and including the end values, to precipitate the α-phase that hardens the titanium alloy.

19. A timepiece or jewellery component according to any one of claims 14 to 18, characterised in that The titanium alloy conforms to the following ranges: 8 ≤ MoE ≤ 11, or even 8.3 ≤ MoE ≤ 10.0; and / or the following ranges: 2.755 < Bo < 2.810 and 2.33 < Md < 2.44, or even 2.758 < Bo < 2.788 and 2.330 < Md < 2.385, or even 2.765 < Bo < 2.775 and 2.36 < Md < 2.38, where MoE is the molybdenum equivalent, and Bo and Md represent the bond order and the average d-orbital energy level respectively.

20. Method for manufacturing a timepiece or jewelry component according to any one of claims 14 to 19, characterized in that The method comprises the step of determining the transformation temperature or the recrystallization temperature of the titanium alloy by mechanical spectroscopy, in particular the nucleation temperature of the ω phase or even the nucleation temperature of the α phase, or even the recrystallization temperature.

21. Method for manufacturing a timepiece or jewelry component according to any one of claims 14 to 20, characterized in that All cooling sub-steps of the thermodynamic treatment are performed by quenching.

22. Method for manufacturing a timepiece or jewelry component according to any one of claims 14 to 21, characterized in that The method comprises a step of finishing by polishing the titanium alloy surface of the component, which produces a polished surface with a total average roughness Rz of less than 90 μm, or even less than 80 μm, or even less than 60 μm; and / or an arithmetic average roughness Ra of less than 15 μm, or even less than 12 μm, or even less than 10 μm.